The Effect of Circuit Games to Physical Fitness On 5th Grade Students of Elementary School in Year 2015 - Ibrahim Sembiring (Universitas Negeri Gorontalo, 2019)
The development of physical fitness in elementary schools is an important matter. This will also determine whether these students will grow and develop optimally. One way that students can train physically with circuit games. The purpose of this study was to study circuit play on fitness in elementary schools in 2015. The method in this study was an experimental method that uses 40-meter Fast Tracking norms, calming elbows, lying down (sitting 30 seconds), jumping upright, running distance far (600 meters). This article discusses how to improve physical classes. The results of the findings of this article can be used as additional references in improving the ability of elementary school students which can be practiced during physical learning and sports extracurricular activities.